Kidney-Pulmonary Crosstalk from Pathophysiological Perspective - Sharifa Audi Salsabila; Alfian Nur Rosyid; Maulana Antiyan Empitu; Ika Nindya Kadariswantiningsih; Satriyo Dwi Suryantoro; Mutiara Rizki Haryati; Mochammad Thaha; Yusuke Suzuki (Faculty of Medicine Universitas Airlangga, 2022)
Lungs and kidneys are distant organs which are functionally related in physiological and pathological contexts. Acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) are common complications in acute kidney injury (AKI) or acute-on-chronic kidney disease. On the other hand, there is a considerable risk of AKI in respiratory diseases such as ARDS and chronic obstructive pulmonary disease (COPD). From a pathophysiological point of view, the kidney-lung crosstalk involves interdependency in the regulation of fluid hemodynamic, acid-base and electrolyte balance, and carbon dioxide partial pressure. Aside from the closely related function, the crosstalk may also occur by non-classical mechanisms such as through activation of systemic inflammation, excessive cytokine release, and the formation of auto-antibody which targets both kidneys and lungs. This review discussed several disease mechanisms by which kidney and lungs affect each other or are simultaneously affected by pathological processes. Particularly, this review discussed some specific mechanisms in lungs and kidneys, such as how hypoxemia and hypercapnia induced by ARDS may reduce kidney function and how distance injury on kidney may affect the development of non-cardiogenic edema lungs.